Radiology structured reporting handbook disease -specific templates and interpretation pearls - Sommer, Wieland H.; Brook, Olga R. (Thieme, 2021)
A practical guide for radiologists on providing high yield disease-specific reports Multiple studies show that referring physicians have a clear preference for structured radiology reports due to clarity and ease of interpretation, yet a one-size-fits all approach does not address disease complexities. Concurrently, the use of structured radiology templates has increased, driven in part by the need to comply with big data and artificial intelligence as well as reimbursement. Standardization of reporting is one of the first essential steps in the transformation of radiology from ""the art of im.